2020
DOI: 10.1101/2020.07.19.210773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Dystonia Gene THAP1 Controls DNA Double Strand Break Repair Choice

Abstract: The Shieldin complex, consisting of SHLD1, SHLD2, SHLD3 and REV7, shields DNA double strand breaks (DSBs) from nucleolytic resection. The end-protecting activity of Shieldin promotes productive non-homologous end joining (NHEJ) in G1 but can threaten genome integrity during S-phase by blocking homologous recombination (HR). Curiously, the penultimate Shieldin component, SHLD1 is one of the least abundant mammalian proteins. Here, we report that the transcription factors THAP1, YY1 and HCF1 bind directly to the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…In prior studies, we and others (4, 10) have identified several transcription factors and epigenetic modifiers that are significantly coenriched with THAP1 on the genome. Most prominent among them are YY1 and HCFC1 (Figure 3E), proteins that interact with THAP1 (4, 24, 25) and co-regulate THAP1-bound genes (4,26).…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, we and others (4, 10) have identified several transcription factors and epigenetic modifiers that are significantly coenriched with THAP1 on the genome. Most prominent among them are YY1 and HCFC1 (Figure 3E), proteins that interact with THAP1 (4, 24, 25) and co-regulate THAP1-bound genes (4,26).…”
Section: Discussionmentioning
confidence: 99%
“…7 Direct YY1/THAP1 interaction has been demonstrated 7 and an YY1/THAP1 co-regulatory model impairing DNA double-stranded break repair has been suggested as a pathomechanism for THAP1-associated dystonia. 8 Additionally, both YY1 and THAP1 play key roles in oligodendrocyte maturation, 7 perhaps relevant to white matter abnormalities on MRI in YY1 patients 1 and microstructural white matter abnormalities on diffusion tensor imaging in THAP1 patients. 9,10 Although speculative at present, these overlapping functions and localizations may provide clues to pathogenesis.…”
Section: Yy1: a New Gene For Childhood Onset Dystonia With Prominentmentioning
confidence: 99%